(untitled) (Encuentros, 2016)
The challenge of being able to harmonize institutional, national and international interests, in order to fulfill the social mission contributing to solving social problems and promoting human development, for which a global context has to be taken into account in the present research. The resurgence of educational internationalization is actually a consequence of this. Its development is founded on the will to enhance the capacity and identity of the university community for internationalization. Theoretically it started setting up the foundations from a qualitative approach, methodologically based on structural and systemic action research to establish the university internationalization strategy. The results show that the proposed strategy is an instrument that has allowed enhancing the development of the internationalization culture, defining objectives and strategies, which from the praxis, are carried out in the respective action plans, measurement criteria, and levels of achievement. Keywords: university internationalization, international cooperation and collaboration, institutional development.